Post-Pandemic Usage of Collaboration Tools: Influencing Factors - Salsabila, Aulia Rido; Wilantika, Nori; Santoso, Ibnu; Choir, Achmad Syahrul (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
The distance existed due to the COVID-19 pandemic drove people to utilize collaboration tools to continue communication, coordination, and collaboration. The increasing use of collaboration tools during WFH impact on our way of working. The collaboration tools also offer efficiencies, allow workers to break silos, and increase the quality of communication at the company-wide level. As we recover from the pandemic, the government revoked the social distancing policy and it is assumed to influence the continued use of collaboration tools as people fully carry out their activities face-to-face again. This study aims to understand the continuance usage of collaboration tools after no more social distancing. This study also seeks to identify the factors influencing the ongoing use of collaboration tools by integrating the Technology Acceptance Model (TAM) and Expectation Confirmatory Model (ECM). The method of data analysis employed was the partial least squares structural equation model (PLS-SEM). The findings indicated that most of 437 respondents kept using collaboration tools after no more social distancing. However, there was a decrease in the frequency of use. Our study findings have also proved that Actual Continued Usage is influenced by Continuance Intention by 43%. Factor that influences continuance intention the most is the attitude toward using collaboration tools, which is influenced by users’ perceived usefulness of the collaboration tools. The results of this study also support the integration of TAM and ECM to examine user intentions and behavior regarding the continuance use of a technology.